An invasive but simple and accurate method for ascending aorta–femoral artery pulse wave velocity measurement. (February 2013) - Kilic, Harun; Yelgec, Selcuk; Salih, Orcan; Akdemir, Ramazan; Karakurt, Ozlem; Cagirci, Goksel; Yeter, Ekrem; Acikel, Sadik; Dogan, Mehmet; Arslantas, Ugur; Baha, Resat Mehmet
Abstract Introduction. Pulse wave velocity (PWV) is an emerging predictor in the assessment of cardiovascular risk in diseased and healthy populations. We suggest a novel method for the accurate measurement of PWV. Method. PWV is calculated from pulse transit time using two separate pulse recordings over a known distance. 8F sheaths were placed in the right femoral arteries and routine coronary angiographies were performed with 5F diagnostic catheters. Ascending aorta pressures were measured with right diagnostic catheter tip in the ascending aorta and synchronous femoral artery pressures were measured with the sheath in the femoral artery. The distance between the two pressure sites was calculated as follows: total length of the right diagnostic catheter−length of the catheter outside the sheath−Sheath length. Results. We evaluated the PWV measured using the catheter method in 24 subjects. PWV correlated positively and independently with age (p = 0.004), coronary artery disease (p = 0.04), ascending aorta systolic pressure (p = 0.006), femoral artery systolic pressure (p = 0.008), ascending aorta pulse pressure (p = 0.003) and femoral artery pulse pressure (p = 0.04). In coronary artery disease patients, the mean PWV value was significantly higher than in patients with normal coronary arteries (12.61 ± 6.31 m/s vs 7.58 ± 2.26 m/s p = 0.04). Conclusion. We describe a novel and accurate but invasive method for measurement of PWV. Our results may serve as a reference for non-invasive assessment of aorta–femoral artery PWV.